ANALISIS PENGARUH MUATAN LEBIH (OVERLOADING) TERHADAP KINERJA JALAN DAN UMUR RENCANA PERKERASAN LENTUR (STUDI KASUS RUAS JALAN RAYA PRINGSURAT, AMBARAWA-MAGELANG) - G. Irwan Simanjuntak; Adri Pramusetyo; Bambang Riyanto; Supriyono Supriyono (Jurnal Karya Teknik Sipil, 2014)
Roads Bawen - Pringsurat, is part of road connecting the center of national economic activities. Highway Bawen - Pringsurat many crossed by heavy vehicles with a charge by overloadin. Besides that also increase traffic on a street Bawen - Pringsurat. From the observation volume of traffic on Bawen - Pringsurat in 2014 is worth 1.462,60 smp /hours with value DS 0,49. The predictions in the 2024 thought to be 2.332,97 smp / hours, so acquired value DS 0,78. An analysis of existing pavement is using two types of burden that is the burden of standard ( with reference to a sum of the load that it allowed or JBI ) and the burden of factual ( the survey ). Burden vehicle standard had class road MST 10 tons while with to load factual in railroad scale it reached MST 12 tons. The result analysis shows pavement existing structure can just hold both overload 5,6 years of age plan for 10 years. Calculation shows that roads Bawen - Pringsurat needed- thick layer by 2,9 cm ( added to load standard ) and to 5.6 cm (added to load factual). Based on the result analysis loads factual in the field and suggested should be on vehicle in 2 directions railroad scale Pringsurat.